Wildlife disease prevalence in human‐modified landscapes. (22nd December 2012) - Brearley, Grant; Rhodes, Jonathan; Bradley, Adrian; Baxter, Greg; Seabrook, Leonie; Lunney, Daniel; Liu, Yan; McAlpine, Clive
ABSTRACT Human‐induced landscape change associated with habitat loss and fragmentation places wildlife populations at risk. One issue in these landscapes is a change in the prevalence of disease which may result in increased mortality and reduced fecundity. Our understanding of the influence of habitat loss and fragmentation on the prevalence of wildlife diseases is still in its infancy. What is evident is that changes in disease prevalence as a result of human‐induced landscape modification are highly variable. The importance of infectious diseases for the conservation of wildlife will increase as the amount and quality of suitable habitat decreases due to human land‐use pressures. We review the experimental and observational literature of the influence of human‐induced landscape change on wildlife disease prevalence, and discuss disease transmission types and host responses as mechanisms that are likely to determine the extent of change in disease prevalence. It is likely that transmission dynamics will be the key process in determining a pathogen's impact on a host population, while the host response may ultimately determine the extent of disease prevalence. Finally, we conceptualize mechanisms and identify future research directions to increase our understanding of the relationship between human‐modified landscapes and wildlife disease prevalence. This review highlights that there are rarely consistent relationships between wildlife diseases and human‐modified landscapes. In addition, variation is evident between transmission types and landscape types, with the greatest positive influence on disease prevalence being in urban landscapes and directly transmitted disease systems. While we have a limited understanding of the potential influence of habitat loss and fragmentation on wildlife disease, there are a number of important areas to address in future research, particularly to account for the variability in increased and decreased disease prevalence. Previous studies have been based on a one‐dimensional comparison between unmodified and modified sites. What is lacking are spatially and temporally explicit quantitative approaches which are required to enable an understanding of the range of key causal mechanisms and the reasons for variability. This is particularly important for replicated studies across different host‐pathogen systems. Furthermore, there are few studies that have attempted to separate the independent effects of habitat loss and fragmentation on wildlife disease, which are the major determinants of wildlife population dynamics in human‐modified landscapes. There is an urgent need to understand better the potential causal links between the processes of human‐induced landscape change and the associated influences of habitat fragmentation, matrix hostility and loss of connectivity on an animal's physiological stress, immune response and disease susceptibility. This review identified no study that had assessed the influence of human‐induced landscape change on the prevalence of a wildlife sexually transmitted disease. A better understanding of the various mechanisms linking human‐induced landscape change and the prevalence of wildlife disease will lead to more successful conservation management outcomes.